On the courses of 1919 of Martin Heidegger: the Phenomenology as original science - Pinto Benavides, Héctor (Revista de Humanidades de Valparaíso, 2014)
This paper aims to describe and present, as approach, the research and intellectual process that develops Heidegger his first lessons in Fribourg (1919), The idea of philosophy and the problem of worldview, in which attempts to set up some idea of philosophy as the original science. At the same time, this paper is intended as a contribution to the dissemination and knowledge of Heidegger’s intellectual stage, which in my opinion, allow a deeper and a comprehensive set of understanding his work and thought.